Calibration of the hydraulic model of the district heating network - Niemyjski , Olgierd (Instal, 2020)
The article presents various aspects of performing calibration of district heating network models. Special attention has been paid to the quality of data control from which the hydraulic model is built. The GIS databases are the source of information about the district heating system. They contain a very wide range of data, but for the purpose of simulation calculations they are not sufficient and other databases characteristic for the district heating industry should be used. The basic criterion for correctness of calibration is to obtain an acceptable correspondence between the calculation results and the pressure measurement results at selected locations of the district heating network. An example of a hydraulic model of pressure loss in a district heating pipeline shows the reasons for discrepancies between the calculation results and the actual values of water parameters. Attention was drawn to the necessity of verification of data describing the model of heat network according to the real state. It is a particular importance for interpretation of calculated values of water pressure in pipelines.
Keywords: modelling of district heating network; calibration of hydraulic model; computer simulation of heating system